Novel clinicopathological characteristics differentiate dementia with Lewy bodies from Parkinson's disease dementia. (12th August 2020) - Hansen, D.; Ling, H.; Lashley, T.; Foley, J. A.; Strand, C.; Eid, T. M.; Holton, J. L.; Warner, T. T.
Abstract : Dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) known as Lewy body dementias have overlapping clinical and neuropathological features. Neuropathology in both includes combination of Lewy body and Alzheimer's disease (AD) pathology. Cerebral amyloid angiopathy (CAA), often seen in AD, is increasingly recognized for its association with dementia. Aims: This study investigated clinical and neuropathological differences between DLB and PDD. Methods: 52 PDD and 16 DLB cases from the Queen Square Brain Bank (QSBB) for Neurological disorders were included. Comprehensive clinical data of motor and cognitive features were obtained from medical records. Neuropathological assessment included examination of CAA, Lewy body and AD pathology. Results: CAA was more common in DLB than in PDD ( P  = 0.003). The severity of CAA was greater in DLB than in PDD ( P  = 0.009), with significantly higher CAA scores in the parietal lobe ( P  = 0.043), and the occipital lobe ( P  = 0.008), in DLB than in PDD. The highest CAA scores were observed in cases with APOE ε4/4 and ε2/4. Survival analysis showed worse prognosis in DLB, as DLB reached each clinical milestone sooner than PDD. Absence of dyskinesia in DLB is linked to the significantly lower lifetime cumulative dose of levodopa in comparison with PDD. Conclusions: This is the first study which identified prominent concurrent CAA pathology as a pathological substrate of DLB. More prominent CAA and rapid disease progression as measured by clinical milestones distinguish DLB from PDD.